2009
DOI: 10.1080/17441690902769669
|View full text |Cite
|
Sign up to set email alerts
|

Integrating quality postnatal care into PMTCT in Swaziland

Abstract: Swaziland's prevention of mother-to-child transmission (PMTCT) programme is linked to maternal and newborn health (MNH) services, but is mainly focussed on HIV/AIDS. Existing MNH services are inadequate, especially postnatal care (PNC) of mothers and babies, with delayed postnatal visits occurring at 4-6 weeks after delivery. Fifty-seven percent of staff in seven Swazi health facilities were trained in promoting and providing early PNC. A final evaluation showed a 20-fold increase in the number of visits comin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…6,8 Low coverage may be partially explained by the initial introduction of PMTCT programs as stand-alone vertical programs. 9–11 In addition, PMTCT interventions create significant additional work for staff in healthcare systems already suffering from insufficient human, financial, and structural resources. 12 Thus, PMTCT implementation is suboptimal and has not produced the expected reduction in MTCT rates.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Low coverage may be partially explained by the initial introduction of PMTCT programs as stand-alone vertical programs. 9–11 In addition, PMTCT interventions create significant additional work for staff in healthcare systems already suffering from insufficient human, financial, and structural resources. 12 Thus, PMTCT implementation is suboptimal and has not produced the expected reduction in MTCT rates.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research in the IMPAACT P1077 PROMISE trial will provide further information in the future as to the best of these approaches to reduce transmission through breastfeeding, and whether stopping prophylactic HAART has any long-term adverse impact on maternal health. Translation of these research findings into real impact depends on the improvement of services to reach and care for HIV-infected mothers and their children [48,7377]. Without significant efforts to improve the coverage and quality of PMTCT services and better use of these to provide access to ongoing treatment for women, we will not achieve the maximum benefit from antiretroviral use in pregnancy in low-resource settings.…”
Section: Resultsmentioning
confidence: 99%
“…4,26-32 In 2009, the NIH Office of AIDS Research identified as a top priority research on how to promote women's linkage to and retention in care at each step of the PMTCT cascade. 33 This study demonstrates that although we are able to enroll more women in HIV care through integration, integration alone does not necessarily translate to improved maternal health outcomes or decreased rates of mother-to-child transmission of HIV, as compared to non-integrated services.…”
Section: Discussionmentioning
confidence: 99%